Trade Shows and SME Internationalisation: Networking for Performance - Stephan Gerschewski; Natasha Evers; Anh Tuan Nguyen; Fabian Jintae Froese (Management International Review, 2020)
Trade shows are a key vehicle where SMEs often develop networks, through which valuable resources for internationalisation can be acquired. However, there tends to be a scarcity of research on the performance outcomes of network development of international SMEs (ISMEs), particularly, in trade show forums. Adopting a network-based view, we investigate the influence of trade shows on the performance of ISMEs. Results from a survey of 229 Australian and New Zealand SMEs indicate that proactiveness is positively associated with the development of networks through trade shows, which, in turn, increases the firms' operational performance, but not financial performance. In addition, the effect of trade shows is generally more beneficial for ISMEs in the service industry, compared to other industries.
Keywords: 330; Small and medium-sized enterprise (SME); Network; Trade show; Internationalisation; Firm performance